Importance of training volume through the use of step trackers apps promoted from the subject of physical education to change body composition, physical fitness and physical activity in adolescents and the influence of gender - Mateo-Orcajada, Adrián; Vaquero-Cristóbal, Raquel; Abenza-Cano, Lucía (Physiology & behavior, 2024)
•High volume training with mobile apps reduces fat mass in adolescents.•The use of mobile apps increase physical activity and curl-up performance, regardless of the training volume.•Mobile apps are an educational resource to promote from physical education subject.•The gender covariate is not influential in the intra-group changes, but it is influential in the inter-group differences.•The distance covered with the apps could not be the most important variable, and other variables should be considered in the future. The aim of the present study was to determine the changes in physical activity level (PA), kinanthropometric and derived variables, and physical fitness in adolescents, as a result of an out-of-school intervention with mobile step tracker apps promoted from the field of physical education, according to the volume of training completed and gender. A randomized controlled trial was carried out with 400 adolescents (210 males and 190 females) aged 12 to 16 years old (mean age: 13.96 ± 1.21 years-old). Adolescents were divided into experimental group (EG) (n = 240) and control group (CG) (n = 160). Two measurements were carried out, separated by a 10-week intervention, and PA, kinanthropometric variables and physical condition were measured. During the intervention, EG must use Strava (n = 74); Pokémon Go (n = 59); Pacer (n = 60); and MapMyWalk (n = 47) a minimum of 3 times per week, covering an incremental distance from 7,000 steps per day (week 1) to 12,500 steps per day (week 10). After that, EG were divided in quartile according to the volume of training completed. The results obtained showed a significant increase between pre-and post in PA (p = 0.009–0.044) and curl-up (p < 0.001–0.040) in EG regardless the quartile of compliance, and a reduction in fat variables (p < 0.001) and an increase in CMJ in 75–100 % compliance group (p = 0.005). The introduction of the covariate gender did not introduce changes in the intra-group evolution. On inter-group differences, differences were only found for the post-test values between 0–25 % Vs 25–50 % and between 50–75 % Vs 75–100 % with the group that completed a longer distance being the one that showed the lowest values in the post-test in both cases. When including the covariate gender, no significant differences were found for either the pre-test or the post-test on either variable. To conclude, a higher training volume with mobile apps seems to be relevant in the increase PA and strength and decrease of fat mass. The gender factor is not influential in the intra-group changes, but it is influential in the inter-group differences.